PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PENDAPATAN PETANI JAGUNG - Khairunnisa Rangkuti; Sasmita Siregar; Muhammad Thamrin; Rui Andriano (AGRIUM: Jurnal Ilmu Pertanian, 2014)
The aims of this study was to determine the effect of socioeconomic factors on the income of corn farmers and to know the corn farming efficiency in Lau Tawar Village, District Tanah Pinem, Dairi. Sampling method used was a random sampling method to take a simple random. Data analysis method used was multiple linear regression analysis. The results of the study based on the results of multiple linear regression analysis were significantly influence between the land and labor of the corn farmer’s income and there is no real influence or not significant between the capital, farming experience and the number of dependents of the corn farmer’s income. And based on the analysis of O/I ratio, maizefarming in the study area has been efficient.  Keywords: socio-economic factors, efficiency, revenue, corn